The hired girl - Schlitz, Laura Amy (Candlewick Press, 2017)
In 1911, when fourteen-year-old Joan Skraggs' teacher gives her a journal on her final day of school, she vows to fill it with words of "truth and refinement." Joan records her thoughts throughout the summer working as a hired hand on a farm in Pennsylvania where she dreams her future can be something more.